Beer, Wine, and Mead as Symbols of Wellbeing among the Peoples of Early Medieval Europe – Phenomenon and its Causes - Gromadka, Tomasz (Vade Nobiscum, tom XXV/2025: Varia, 2025)
The article examines the symbolic role of alcohol in the literature of ancient Germanic, Slavic, and Finnish peoples. While excessive drinking was sometimes criticized, alcohol was more often portrayed as a symbol of wellbeing and earthly felicity. Feasting scenes represented harmony and divine favor, while their disruption signaled decline and misfortune. Unlike other pleasures, alcohol held special meaning due to its perceived supernatural origin. Myths such as the Germanic story of Kvasir and the Finnish tale of Osmotar suggest a belief in the otherworldly nature of fermentation, whose spontaneous bubbling was seen as the work of spirits or gods. As a result, alcohol was valued as a unique gift from the divine. This symbolic dimension persisted through Christianization, even after its mythological roots were forgotten.